THE GROWTH AND PRODUCTION OF DWARF ELEPHANT GRASS (Pennisetum purpureum cv. Mott) TOWARDS VARIOUS SLURRY AND BIO-SLURRY FERTILIZER LEVELS - R.D.P, Turusy; Budiasa, I K.M.; Suranjaya, I G. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
This research aimed at determining the effect of cattle-manure slurry fertilizer type and dosage towards the growth and production of dwarf elephant grass. This research was conducted in Greenhouse of the Laboratory, Research Station of Animal Husbandry Faculty of Udayana University on Sesetan Street, Denpasar for 3 months. This research used Fully Randomized Design 2 × 6 factorial design. The first factor was the slurry consisted of P 1 : cattle-manure slurry and P 2 cattle-manure bio-slurry. Meanwhile, the second factor was the dosage of fertilizer consisted of D 5 = 5 ton/ha; D 10 = 10 ton/ha; D 15 = 15 ton/ha; D 20 – 20 ton/ha; D 25 = 25 ton/ ha dan D 30 = 30 ton/ha. Those two factors resulted 12 combinations of treatment. P1D5, P1D10, P1D15, P1D20, P1D25, P1D30, P2D5, P2D10, P2D15, P2D20, P2D25, P2D30. Therefore there were 12 combination treatments repeated four times and there were 48 research. The variables in this research were growth, production, and characteristic. The result showed that the effect of fertilizer type, slurry organic and cattle-manure bio-slurry, toward all variables of dwarf elephant grass growth ( Pennisetum purpureum cv.Mott) and production were not significantly different (P>0,05). The effect of fertilizer level toward branch length, dry weight total forage, and leaf width showed significantly different result (P<0,05). Based on the results, it can be concluded that the distribution of slurry and bio-slurry organic fertilizer gave results that were not significantly different from the growth and production of  dwarf elephant grass. The distribution of slurry fertilizer and cattle-manure bio-slurry on the level 25 ton/ha gives the best result toward the growth and production of dwarf elephant grass. There is no interaction between the type of fertilizer and the dosage of fertilizer.   Keywords: slurry, bio-slurry, pennisetum purpureum cv.Mot t .